Skuld, ansvar och tillräknelighet - Bettina Schütz-Gärdén (Nordisk Tidsskrift for Kriminalvidenskab)
The Swedish penal system regarding mentally ill or disturbed offenders differs from those of most other countries by having abolished the concept of criminal incapacity for acts committed under mental defects ("plea of not guilty by reason of insanity ") in 1965. As of now, the mentally ill are judged and sentenced under the ordinary criminal rules and procedures, though imprisonment is excluded as a possible sanction. The current system has been criticised, however, since its introduction, and in 1996, a parliamentary committee proposed to re-establish mental incapacity in criminal law. This proposal is at present under further evaluation.